2007
DOI: 10.1002/art.22928
|View full text |Cite
|
Sign up to set email alerts
|

Type I interferon–inducible gene expression in blood is present and reflects disease activity in dermatomyositis and polymyositis

Abstract: Objective. To apply gene expression profiling to the study of peripheral blood mononuclear cells from patients with inflammatory myopathies, in order to provide insight into disease pathogenesis and identify potential biomarkers associated with disease activity.Methods. We used Affymetrix whole-genome microarrays to measure the expression of ϳ38,500 genes in 65 blood and 15 muscle samples from 44 patients with dermatomyositis (DM), polymyositis (PM), inclusion body myositis (IBM), myasthenia gravis, or genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 270 publications
(214 citation statements)
references
References 20 publications
11
198
0
5
Order By: Relevance
“…Microarray gene expression profiling has detected upregulation of genes for adhesion molecules, cytokines, MHC class I molecules, chemokines and immunoglobulins in the muscles of patients with inflammatory myopathies [4,[53][54][55][56].In particular, the interferons (IFNs)and IFN-inducible genes have been strongly implicated in the pathogenesis of myositis. The enhanced type I IFN gene signature has been associated with disease activity in both PM and DM [57].Additionally,immunostaining for type I IFN has been detected in DM in muscle fibres in areas showingperifascular atrophy, as well as in plasmacytoid dendritic cells and in the capillary endothelial cells [27,58]. In contrast,overexpression of the type IIIFN (IFN-ƴ)…”
Section: Cytokine and Chemokine Involvementmentioning
confidence: 99%
“…Microarray gene expression profiling has detected upregulation of genes for adhesion molecules, cytokines, MHC class I molecules, chemokines and immunoglobulins in the muscles of patients with inflammatory myopathies [4,[53][54][55][56].In particular, the interferons (IFNs)and IFN-inducible genes have been strongly implicated in the pathogenesis of myositis. The enhanced type I IFN gene signature has been associated with disease activity in both PM and DM [57].Additionally,immunostaining for type I IFN has been detected in DM in muscle fibres in areas showingperifascular atrophy, as well as in plasmacytoid dendritic cells and in the capillary endothelial cells [27,58]. In contrast,overexpression of the type IIIFN (IFN-ƴ)…”
Section: Cytokine and Chemokine Involvementmentioning
confidence: 99%
“…Recent microarray studies have pointed toward a mechanism of tissue injury associated with the overexpression of type 1 interferoninducible gene [123,124]. Interferon-stimulated gene 15 (ISG15) conjugated proteins in DM muscle with muscle perifascicular atrophy, were investigated by Salajeheh et al [123].…”
Section: Dermatomyositis With Muscle Perifascicular Atrophymentioning
confidence: 99%
“…These studies have shown marked overexpression of type 1 IFN-inducible genes in DM but not PM or IBM muscle. 22 Marked overexpression of type 1 IFN-inducible genes has also been observed in the blood of patients with DM or PM, 23 and in patients with systemic lupus erythematosus (SLE). 24,25 A previous cross-sectional and paired-visit study of 28 patients with DM, PM and IBM showed that type 1 IFN-inducible genes were the highest differentially expressed genes in DM and PM blood samples compared with normal controls.…”
Section: Introductionmentioning
confidence: 99%